"Migrants Are Splendid Types": The "Beautiful Balts" Megamarketing Campaign to Boost the Reception of Displaced Persons in Australia after World War II. (December 2018) - Krisjanous, Jayne; Kadirov, Djavlonbek
Human migration is often a result of flight from post-conflict socio-economic disintegration, where dysfunctional marketing systems exacerbate the suffering of people. Despite the potential trauma and disruption incurred, a move away to systems perceived to be better are favored. Using a historical research approach, this article focuses on the end of World War II that heralded an unprecedented humanitarian crisis involving millions of displaced persons, marshalled in Displaced Persons' (DP) Camps. This investigation focuses on the "Beautiful Balts" megamarketing campaign in Australia, the promotion of a handpicked consignment of DPs from the Baltic States of Lithuania, Latvia and Estonia to host-to-be communities, in order to satisfy the economy's growing need for fresh industrial labour input. The authors argue that this campaign was crucial in dismantling the "white only" frame through the use of the hitherto undocumented process of frame demystification. This campaign set the stage for the opening up of Australia to greater numbers of post-WWII DP migrants from different ethnicities and fundamental changes to beliefs and practices that configured Australian marketing systems of the day.